Gastric motor and sensory function in health assessed by magnetic resonance imaging: Establishment of reference intervals for the Nottingham test meal in healthy subjects. Issue 12 (14th September 2018) - Parker, Helen; Hoad, Caroline L; Tucker, Emily; Costigan, Carolyn; Marciani, Luca; Gowland, Penny; Fox, Mark
Abstract: Background: Current investigations of gastric emptying rarely identify the cause of symptoms or provide a definitive diagnosis in patients with dyspepsia. This study assessed gastric function by magnetic resonance imaging (MRI) using the modular "Nottingham test meal" (NTM) in healthy volunteers (HVs). Methods: The NTM comprises (a) 400 mL liquid nutrient (0.75 kcal/mL) labeled with Gadolinium‐DOTA and (b) an optional solid component (12 agar‐beads [0 kcal]). Filling sensations were documented. MRI measurements of gastric volume, emptying, contraction wave frequency, and secretion were obtained using validated methods. Key Results: Gastric function was measured in a population of 73 HVs stratified for age and sex. NTM induced moderate satiety and fullness. Labeled fluid was observed in the small bowel in all subjects after meal ingestion ("early‐phase" GE). Secretion was rapid such that postprandial gastric content volume was often greater than meal volume (GCV0 > 400 mL), and there was increasing dilution of the meal during the study ( P  < 0.001). Gastric half‐time was median 66‐minutes (95% reference interval 35 to 161‐minutes ["late‐phase" GE]). The number of intact agar beads in the stomach was 7/12 (58%) at 60‐minutes and 1/12 (8%) at 120‐minutes. Age, bodyweight and sex had measurable effects on gastric function; however, these were small compared to inter‐individual variation for most metrics. Conclusions and Inferences: Reference intervals are presented for MRI measurements of gastric function assessed for the mixed liquid/solid NTM. Studies in patients will determine which metrics are of clinical value and also whether the reference intervals presented here offer optimal diagnostic sensitivity and specificity. Abstract : Liquid gastric emptying reference intervals for the (A) 400mL liquid‐ and (B) mixed‐Notthingham Test Meals. Volume iat t=0 was often >400mL due to secretion. The impact of the modular, non‐nutrient solid component had minimal effect on gastric emptying. A single metric (e.g. half time) is not sufficient to describe the dynamic volume change.